Cutting Through the Noise: Bacterial Chemotaxis in Marine Microenvironments - Brumley, Douglas R.; Carrara, Francesco; Hein, Andrew M.; Hagstrom, George I.; Levin, Simon A.; Stocker, Roman (Frontiers in Marine Science, 2020)
The ability of marine microbes to navigate towards chemical hotspots can determine their nutrient uptake and has the potential to affect the cycling of elements in the ocean. The link between bacterial navigation and nutrient cycling highlights the need to understand how chemotaxis functions in the context of marine microenvironments. Chemotaxis hinges on the stochastic binding/unbinding of molecules with surface receptors, the transduction of this information through an intracellular signalling cascade, and the activation and control of flagellar motors. The intrinsic randomness of these processes is a central challenge that cells must deal with in order to navigate, particularly under dilute conditions where noise and signal are similar in magnitude. Such conditions are ubiquitous in the ocean, where nutrient concentrations are often extremely low and subject to rapid variation in space (e.g. particulate matter, nutrient plumes) and time (e.g. diffusing sources, fluid mixing). Stochastic, biophysical models of chemotaxis have the potential to illuminate how bacteria cope with noise to efficiently navigate in such environments. At the same time, new technologies for experimentation allow for continuous interrogation -- from milliseconds through to days -- of bacterial responses in custom dynamic nutrient landscapes, providing unprecedented access to the behaviour of chemotactic cells in microenvironments engineered to mimic those cells navigate in the wild. These recent theoretical and experimental developments have created an opportunity to derive population-level uptake from single-cell motility characteristics in ways that could inform the next generation of marine biogeochemical cycling models.